A Tertiary Care Hospital's Observations on the Prevalence and Antibiotic Sensitivity of the Most Common Organisms Causing Urinary Tract Infections in Children - Miraj Ahmad, Shaikh Fahad Falah, Aina Khurshid, Sehrish Khan, Muhammad Faraz Shamshad, Shahidullah, Sudhair Abbas Bangash, Aqsa Khalid7, Muhammad Irfan Fareed, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research was to evaluate the antibiotic resistance profile of urinary tract infection-causing bacteria and their prevalence among children presenting to a tertiary care hospital. Study Design: Cross-sectional/ Descriptive study Place and Duration: This study was carried out at Khyber Teaching Hospital, Peshawar from June, 2021 to May 2022. Methods: Total 112 suspected cases (children) of UTI with ages 6-months to 14 years were presented. After receiving parental agreement, we documented the children's age, gender, residence, and parental education level.It was decided to perform a urine dipstick test to check for nitrites and leucocytes, and then analyze the leucocytes and bacteria under the microscope. Antimicrobial resistance was tested using the modified Kirby-Bauer disc diffusion technique with a panel of antimicrobials.SPSS 20.0 was used to analyze all data. Results: Among 112 included cases, 58 (51.8%) were males and the rest were 54 (48.2%) female children. Frequency of leucocytes and nitrites by urine dipstick method was 30 (26.8%) and 12 (10%) but under the microscope, number of leucocytes were 15 (13.4%) and bacteria was 9 (8.03%). There were 65 (58.04%) gram positive and majority were females and 47 (41.96%) were gram negative cases. We found E.coli was the most prevalent microorganism found in 46 (70.8%) cases, 5 (7.7%) Klebsiella spp. and Pseudomonas spp. was 4 (6.2%). We found that microorganism were highly resistant (100%) to antibiotics ceftazidime, cefoperazone, ampicillin and ofloxacin while ciprofloxacin, cefuroxime and ceftriaxone showed high sensitivity. Conclusion: We observed that E.coli was the most frequent bacteria in UTI urine samples. Antimicrobial resistance in UTI-causing pathogens is worrying. It's crucial to monitor UTI-causing microbes' antibiotic susceptibility trends. Keywords:UTI, E.coli, Klebsiella spp., Resistance, Sensitivity